2015
DOI: 10.11144/javeriana.iyu19-1.tdkp
|View full text |Cite
|
Sign up to set email alerts
|

Cinética de degradación térmica de poliácido láctico en múltiples extrusiones

Abstract: Se muestran los resultados del estudio cinético de la degradación térmica del Poliácido Láctico – PLA, sin procesar y reprocesado por extrusión. Las muestras procesadas se obtenían después de cada reprocesamiento. Estas muestras se analizaron respecto a la temperatura de transición vítrea, índice de fluidez, poder calorífico y termogravimetría dinámica. Se determinó el triplete cinético por medio de los métodos Flynn-Wall-Ozawa (FWO), Friedman, Gyulai, Kissinger-Akahira-Sunose (KAS), Kissinger, Diferencial e I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…Obtained results of activation energy of thermal decomposition of ABS, PLA, and PA12 are similar to those presented in previous studies. The value calculated for ABS is less than 3% lower than reported, [59] for PLA is less than 0.5% lower than reported, [58] and for PA12 is slightly over 4% than reported. [56] Only the value of activation energy of thermal decomposition of ULTEM found in the literature, calculated with the CR method, is over 30% higher than calculated in this work.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…Obtained results of activation energy of thermal decomposition of ABS, PLA, and PA12 are similar to those presented in previous studies. The value calculated for ABS is less than 3% lower than reported, [59] for PLA is less than 0.5% lower than reported, [58] and for PA12 is slightly over 4% than reported. [56] Only the value of activation energy of thermal decomposition of ULTEM found in the literature, calculated with the CR method, is over 30% higher than calculated in this work.…”
Section: Resultscontrasting
confidence: 52%
“…In addition, another study reports that calculating activation energy with different methods may give different values, even for the same TG data: activation energy of PLA thermal decomposition was from 141 to 299 kJ mol À1 . [58] This range of values raises the question of the real value of this parameter and the selection of the appropriate calculation method. However, the aim of this work was not to determine the absolute value of activation energy for each material, but to determinate the correlation between activation energy of thermal decomposition of the substrates and activation energy of silver nanopowder sintering process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in view of the rising interest towards polymer nanocomposites, due to their improved mechanical thermal and barrier properties [79,80], some researchers have recently studied the of recycling biobased nanocomposites [19,63,81]. With particular reference to PLA, it is known that this polymer undergoes thermodegradation during melt processing [76,82] and, therefore, its recyclability is strictly related to the actual extent of thermodegradative phenomena during melt processing [76,83,84]. For instance, Tesfaye et al [81] investigated the effect of silk nanocrystals (SNC) on thermal and rheological properties of PLA subjected to repeated extrusion operations; they found that the presence of SNC slows down the thermal degradation of PLA.…”
Section: Recycling Of Systems Based On Biodegradable Polymersmentioning
confidence: 99%
“…According to Bouamoud and collaborators, 66 this shi is due to the temperature gradient during the reaction process, which is smaller at low heating rates and larger at a high heating rates, that is, the increase in the heating rate causes a delay in material degradation. 67 However, this behavior was not observed in the OC1NS sample, since there was a decrease in the maximum temperatures between the heating rates of 15 and 20 C min À1 . The action of the catalysts in decreasing the maximum temperature, when compared to the maximum temperatures of coconut oil alone, was observed in samples OC1NS and OC5NS at all three heating rates.…”
Section: Thermal and Kinetic Studymentioning
confidence: 95%